Empagliflozin reduces TNFa-induced reactive oxygen species through inhibition of the human endothelial Na+/H+ exchanger 1. (14th October 2021) - Uthman, L; Baumgart, P; Baartscheer, A; Schumacher, C.A; Li, X; Hermanides, J; Preckel, B; Hollmann, M.W; Coronel, R.C; Zuurbier, C.J; Weber, N.C
Abstract: Background: Chronic low-grade inflammation, endothelial dysfunction and oxidative stress are major interactive pathways contributing to the pathogenesis of HFpEF. The sodium/glucose cotransporter 2 (SGLT2) inhibitor Empagliflozin (EMPA) inhibits inflammation-induced ROS generation in endothelial cells. EMPA also lowers Na+/H+ exchanger 1 (NHE1) activity and cytoplasmatic Na+ levels ([Na+]c) in cardiomyocytes. Purpose: It is unknown how inflammation causes oxidative stress in endothelial cells and how EMPA can mitigate this. Here we examined for human endothelial cells whether 1) inflammatory mediators activate NHE1 activity, 2) increased [Na+]c mediates the inflammation-induced ROS production, and 3) EMPA reduces inflammation-induced ROS through NHE1 inhibition. Methods: Human umbilical vein endothelial cells (HUVECs) and human coronary artery endothelial cells (HCAECs) were incubated with vehicle (V), 10ng/mL TNFα, 1μM EMPA or the canonical NHE1 inhibitor 10μM Cariporide. NHE1 activity was measured using the intracellular pH sensitive seminaphtharhodafluor fluorescence, by the pH recovery rate after an ammonium pulse. Intracellular ROS were detected by fluorescent live cell imaging in the presence of 10ng/mL TNFα or under increased Na+ conditions using 100nM ouabain (partial inhibition of the Na+/K+ pump). [Na+]c was measured using the sodium-binding benzofuran isophthalate 1 fluorescent probe. Results: TNFα enhanced NHE1 activity in HCAECs (Fig a, in Δ[H+]/sec, V 0.81±0.14, TNFα 1.86±0.35 p<0.05). Increasing [Na+]c by ouabain elevated ROS generation (Fig b, in mM, HUVECs; V 5.6±1.3, ouabain 25.2±1.6 p<0.001, HCAECs; V 18.5±2.4, ouabain 91.2±32.6 p<0.05). EMPA reduced NHE1 activity in HUVECs (in Δ[H+]/sec, V 3.55±0.54, EMPA 1.66±0.25 p<0.01 vs V, Cariporide 0.95±0.11 p<0.001 vs V). HCAECs showed similar results. EMPA lowered [Na+]c (HUVECs; from 8.8±0.9 to 6.0±0.5 mM, p<0.05, HCAECs; from 7.8±0.7 to 4.0±0.8 mM, p<0.001). ROS generation was reversed in the presence of EMPA and/or Cariporide indicating that the effect was mediated by NHE inhibition (Fig c). Conclusions: TNFα induces oxidative stress in EC through NHE1 activation and the consequently increased [Na+]c. EMPA acutely inhibits TNFα-induced ROS generation by inhibiting NHE1 and lowering [Na+]c in human cardiac and non-cardiac endothelial cells. Our data suggest that the previously reported cardiac effects of EMPA on NHE1 and [Na+]c are also present in endothelial cells. Endothelial ion homeostasis may be a valuable target to reduce inflammation-induced ROS generation and can constitute the pathway through which SGLT2 inhibitors offer protection in HFpEF patients, as examined in the EMPEROR-Preserved trial. Funding Acknowledgement: Type of funding sources: None.